2020
DOI: 10.3390/jof6040303
|View full text |Cite
|
Sign up to set email alerts
|

Neuroparacoccidioidomycosis: A 13-Year Cohort Study, Rio de Janeiro, Brazil

Abstract: Neuroparacoccidioidomycosis (NPCM) is a rare and severe clinical presentation of paracoccidioidomycosis (PCM). We performed a retrospective cohort study at the Evandro Chagas National Institute of Infectious Diseases (INI/Fiocruz), a reference center for PCM in the state of Rio de Janeiro, Brazil. All cases of PCM admitted to the INI/Fiocruz from January 2007 to December 2019 were reviewed. Eight (3.9%) among 207 patients met the diagnostic criteria for NPCM. The mean age was 44.6 years and the male:female rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The lungs are involved in more than 90% of the cases. However, central nervous system (CNS) involvement is reported in 10 to 27% of the cases and is mainly associated with pulmonary manifestations of the disease [11,12]. Both cases of chronic disease reported in this manuscript had disseminated lung lesions, with repercussions on the patients' respiratory capacity (permanent sequelae).…”
Section: Discussionmentioning
confidence: 76%
“…The lungs are involved in more than 90% of the cases. However, central nervous system (CNS) involvement is reported in 10 to 27% of the cases and is mainly associated with pulmonary manifestations of the disease [11,12]. Both cases of chronic disease reported in this manuscript had disseminated lung lesions, with repercussions on the patients' respiratory capacity (permanent sequelae).…”
Section: Discussionmentioning
confidence: 76%
“…One more study was excluded after a review of the full text because of insufficient patient data. In conclusion, we included 34 manuscripts, with 104 new cases of NPCM 2,6,12,14–44 . We present the flow diagram in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Many patients developed sequelae 44 . Delay in diagnosis can cause more sequelae 44 . Pedroso et al showed that approximately 63% of the patients had sequelae 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Most of the cases presents with multifocal disease manifested as increased intracranial pressure and seizures. [ 3 ] The CNS involvement is due to hematogenic dissemination from peripheral foci. [ 15 ] PCM and neuroparacoccidioidomycosis (NPCM) are more prevalent in males in a 11:1 ratio.…”
Section: Introductionmentioning
confidence: 99%